Dynamics of microbial necromass in response to reduced fertilizer application mediated by crop residue return. (February 2022) - Ma, Xuesong; Zhang, Wei; Zhang, Xiaochen; Bao, Xuelian; Xie, Hongtu; Li, Jie; He, Hongbo; Liang, Chao; Zhang, Xudong
Abstract: Understanding the response of microbial-derived nitrogen (N) in the soil to N availability is essential for optimizing N fertilizer management. In this study, based on amino sugar biomarker assays in a conservation tillage agroecosystem, we evaluated the effects of 3-year fertilizer N reduction (reduced from 240 to 190, 135, 0 kg N ha −1 ) and crop residue return on microbial necromass N dynamics. The stock of microbial necromass N declined with the decrease of N input, and the decline of bacterial necromass was greater than that of fungal necromass. However, the decrease of 7.3% in microbial necromass N following the cessation of fertilization indicated a dominant role of microbial necromass in soil N retention despite its compensation ability for N demand. Maize residue return alleviated N deficiency in the soil-crop system and favored the maintenance of the soil organic N pool by preferentially improving the net accumulation of fungal necromass. Highlights: Microbial necromass dynamics were interactively controlled by N and C availability. Microbial necromass decomposes supplying soil N. Bacterial necromass was apt to degrade more than fungal necromass under N deficiency. Maize residue return favored retention and stabilization of microbial necromass N.